Ocular alignment, media, and eyelid disorders in Down syndrome. (2nd January 2020) - Makateb, Ali; Hashemi, Hassan; Farahi, Azadeh; Mehravaran, Shiva; Khabazkhoob, Mehdi; Asgari, Soheila
ABSTRACT: Background: Determining the age and gender distribution of ocular disorders in Down syndrome patients aged 10 to 30 years. Methods: In this study, 226 of 250 invited patients through special needs schools, the National Down Syndrome Society, and relevant nonprofit organizations were included. In Noor Eye Hospital, the patients underwent a complete eye examination by a general ophthalmologist and suspect cases were reexamined by a sub-specialist. Examinations included ocular alignment, conjunctiva, eyelid, lacrimal system, cornea, iris, and lens assessment. Results: Mean age of participants was 16.05 ± 4.82 years and 53.0% were male. The most common ocular abnormalities were blepharitis (81.9%, 95% CI:78.0 to 85.3), lens opacity (37.8%, 95% CI:33.3 to 42.3), strabismus (23.4%, 95% CI:19.5 to 27.4; 21.2% esotropia, 0.9% exotropia, and 1.8% dissociated vertical deviation), floppy eyelid (19.9%, 95% CI:16.3 to 23.9), posterior embryotoxon (17.7%, 95% CI:14.2 to 21.2) and nystagmus (11.7%, 95% CI:8.9 to 15.0). Based on independent sample t test, the prevalence of nystagmus ( P = .041) and congenital lens opacity  (P<0.001) significantly increased with age. There was no significant inter-gender difference in the prevalence of any of the studied disorders by chi-square test. Conclusion: In young patients with Down syndrome, the prevalence of ocular pathologies appears to be high and increase with aging. It can be resulted from the cumulative prevalence of undiagnosed or untreated cases. Findings of the study can be a reliable reference for health policy in terms of screening for eye disease and addressing eye care needs.